Neglected nontoxic multinodular goiter presented as a large neck mass. Issue 3 (20th December 2016) - Papadatos, Stamatis S.; Mylonas, Stefanos; Zissis, Christos; Galani, Vasiliki
Key Clinical Message: Large multinodular goiters, obvious to the naked eye, are rarely confronted by clinicians nowadays; yet they do have a place in the differential diagnosis of the neck masses. Due to the fact that 80% of the neck masses in adults are related to malignancy, the later should be ruled out. Abstract : Large multinodular goiters, obvious to the naked eye, are rarely confronted by clinicians nowadays; yet they do have a place in the differential diagnosis of the neck masses. Due to the fact that 80% of the neck masses in adults are related to malignancy, the later should be ruled out.